Five cases of intracranial tuberculoma followed by serial computerised tomography. Issue 4 (April 1979) - Peatfield, R C; Shawdon, H H
Abstract : Five cases of intracranial tuberculoma in Asian adults are described, all of whom presented with epilepsy. The computerised tomographic (CAT) scanner displayed the lesions particularly well, and their characteristics are described. Only two cases were explored surgically, but triple antituberculous chemotherapy has the scan abnormalities in all of them to resolve completely. It is concluded that Asian patients with lesions likely to be tuberculous should be given a trail of antituberculous drugs, and only explored if they should deteriorate clinically, or if the lesion should fail to respond on serial scans.